Penerapan Terapi Storytelling Terhadap Kecemasan Pada Anak Dengan Leukemia Di Bangsal Flamboyan 9 RSUD Dr. Moewardi Surakarta - Nur Sita Dwi Jayanti; Maryatun Maryatun; Lin Marhamah Azizah (STIKes Ibnu Sina Ajibarang, 2023)
Background: Children with leukemia are prone to experience anxiety due to various factors, one of which chemotherapy can cause some side effects such as nausea, vomiting and pain that can add stress in children. Storytelling therapy is used as a non-pharmacological therapy for reduce anxiety in children with leukemia. Very storytelling therapy effectively given to children who have limited energy to play. Purpose: to know the results of the application of therapy storytelling of anxiety in children with leukemia in the Flamboyan 9 RSUD Dr. Moewardi Surakarta. Method: the type of research used is descriptive using the case study method. Anxiety in children is measured with the Hamilton Anxiety Rating Scale (HARS) instrument. Findings: after done application there is a change in anxiety in both respondents from before application in the category of moderate anxiety and after implementation in the mild anxiety category. Implication: there is a changein anxiety in both respondents, storytelling therapy can reduce anxiety in children with leukemia.